Respirable dust and silica exposure among World Trade Center cleanup workers. Issue 3 (4th March 2017) - Pavilonis, Brian T.; Mirer, Franklin E.
ABSTRACT: The cleanup effort following the destruction of the World Trade Center (WTC) was unprecedented and involved removal of 1.8 million tons of rubble over a nine-month period. Work at the site occurred 24 hr a day, 7 days a week and involved thousands of workers during the process. The Occupational Safety and Health Administration (OSHA) conducted personal and area exposure sampling during the cleanup of the site. Secondary data analysis was performed on OSHA air sampling data for respirable dust and silica from September 2001 to June 2002 at the WTC recovery site to characterize workers' exposure. Results for silica and respirable particulate were stratified by area and personal samples as well as job task for analysis. Of 1108 samples included in the analysis, 693 were personal and 415 were area. The mean result for personal silica samples was 42 μg/m 3 (Range: 4.2–1800 μg/m 3 ). Workers identified as drillers had the highest mean silica exposure (72 μg/m 3 ; range: 5.8–800 μg/m 3 ) followed by workers identified as dock builders (67 μg/m 3 ; range: 5.8–670 μg/m 3 ). The mean result for personal samples for respirable particulate was 0.44 mg/m 3 (range: 0.00010–13 mg/m 3 ). There were no discernable trends in personal respirable dust and silica concentrations with date.